Sosialisasi Pemanfaatan Limbah Rumah Tangga untuk Budidaya Maggot dan Pupuk Organik Cair Pada Kegiatan KKN 133 FKIP di Kelurahan Kenep Sukoharjo - Pellu, Musa; Dian Gegana, Theofillus; Bagus Nofrendi, Erian Rahayu Adi; Hanifah, Shofi; Nurul Majid, Khildatus Sakinah; Nailussa’adah, Laila; Oktaviani, Wulan; Rahayu Safitri, Mahaya; Fadilah, Nurul; A’yunin Nisaa, Luthfiana (Edumedia Solution, 2023)
The Community Service Program (Kuliah Kerja Nyata - KKN) conducted by the Faculty of Education and Teacher Training (FKIP) UNS 133 in Kenep Village, Sukoharjo, aims to bring about positive change while enlightening the local community. One of the initiatives implemented by the KKN 133 Kenep group to address the issue of accumulating household waste is a socialization program on the utilization of household waste through maggot cultivation and the production of liquid organic fertilizer (LOF). The implementation method employed for this program is a participatory approach, where KKN students directly engage in the field with the necessary equipment. Students not only provide theoretical explanations about the household waste processing procedures but also involve residents in hands-on practices. This includes providing tools and materials, as well as demonstrating the correct steps. This method is considered highly effective as it allows residents to witness, understand, and experience the benefits of the activities directly. The response from the community during the execution of this service activity has been overwhelmingly positive. The residents not only receive information but actively participate in practical learning processes. The impact of this initiative is significant, contributing to the increased knowledge of the community regarding household waste management, with the hope that this knowledge will be utilized effectively.